Evaluation of Role of Hepatitis C Virus in the Pathogenesis of Hodgkin Lymphoma Patients - Hadi Meeran Hussain, Manzar Zakaria, Qasim Raza, Farooq A Malik, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Hepatitis C is a viral infection that cause liver’s inflammation. Numerous studies have found a significant frequency of hepatitis C virus (HCV) infection in non-lymphoma Hodgkin's patients. B-cell non-Hodgkin's lymphoma (B-NHL) development could be significantly caused by HCV. The purpose of the current study was to investigate the hepatitis C virus role in the pathogenesis Hodgkin lymphoma patients. Patients and Methods: This prospective study was carried out on 60 B-cell non-Hodgkin's lymphoma. (B-NHL) and 30 (healthy) control group in PAF Hospital Lahore Department of Internal Medicine and Oncology Department CMH, Lahore from May 2022 to October 2022. Study protocol was approved by institute ethical committee. Each individual provided written informed consent. All the patients were subjected to history taking, clinical examination, CBCs, kidney and liver function assessment, B2 microglobine, erythrocyte sedimentation rate determination, serum uric acid, abdominal ultrasound for lymphadenopathy and organomegaly, serum LDH, proper diagnosis and staging through CT abdomen, PCR, biopsy of bone marrow, and ELISA. Data analysis was done using SPSS version 27. Results: Of the total 60 B-NHL patients, there were 32 (53.3%) male and 28 (46.7%) females. The overall mean age was 42.8± 10.8 years with an age range 16-65 years. There were 20 (66.7%) male and 10 (33.3%) females in control group and their mean age was 28.4± 11.6 years with an age range 12-60 years. Based on ELISA test, the incidence of for positive and negative anti-HCV antibodies were 34 (56.7%) and 26 (43.3%) respectively. The incidence of positive and negative anti-HCV RNA was 36 (60%) and 24 (40%) respectively. Conclusion: The present study revealed that higher incidence of HCV infection play significant role in the pathogenesis of Hodgkin’s lymphoma patients. This increases the likelihood of HCV infection playing a role in the development of B-NHL. Keywords: Hepatitis C virus, Hodgkin lymphoma, Pathogenesis